1996
DOI: 10.1037/0735-7044.110.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of brainstem motor nuclei blocks expression but not acquisition of the rabbit's classically conditioned eyeblink response.

Abstract: Rabbits were eyeblink conditioned while their accessory abducens nucleus (ACC), facial nucleus (FN), and surrounding reticular formation (RF) were temporarily inactivated with microinjections of muscimol to determine whether these structures are critically involved in acquisition of the conditioned eyeblink response (CR). Rabbits performed no CRs or unconditioned responses (URs) during inactivation training. Training was continued without inactivation and rabbits performed the CR at asymptotic levels from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…This finding extends the results of Zhang and Lavond (1991) who found that cooling the facial nucleus abol- ished completely facial EMG CRs and URs. The present study demonstrated that this effect is also true of NM CRs and URs and is consistent with studies using reversible muscimol lesions of the facial nucleus, which also abolish completely NM responses (Krupa et al 1996). Several conclusions can be made from the electrophysiological results of the present study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding extends the results of Zhang and Lavond (1991) who found that cooling the facial nucleus abol- ished completely facial EMG CRs and URs. The present study demonstrated that this effect is also true of NM CRs and URs and is consistent with studies using reversible muscimol lesions of the facial nucleus, which also abolish completely NM responses (Krupa et al 1996). Several conclusions can be made from the electrophysiological results of the present study.…”
Section: Discussionsupporting
confidence: 78%
“…As a control, we also cooled the facial nucleus during recording from the pontine nuclei. The facial nucleus is critically involved in the expression of both the eye-blink CR and UR (Cegavske et al 1976), although it is not critical for the formation of the conditioned response (Krupa et al 1996;Clark et al 1997;A.A. Zhang and D.G.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying learning-specific plasticity in the cerebellar deep nuclei may involve changes in neuronal excitability or synaptic potentiation (Aizenman & Linden, 2000;Racine, Wilson, Gingell, & Sunderland, 1986). The output of the learning circuitry is the projection from the deep nuclei to the red nucleus, and from there to the relevant motor nuclei (Chapman, Steinmetz, Sears, & Thompson, 1990;Clark & Lavond, 1993;Desmond, Rosenfield, & Moore, 1983;Krupa & Thompson, 1995;Krupa, Thompson, & Thompson, 1993;Krupa, Weng, & Thompson, 1996;McCormick, Guyer, & Thompson, 1982;.…”
Section: Introductionmentioning
confidence: 99%
“…In simple delay classical conditioning of the rabbit nictitating membrane response, neural unit activity that models the learned behavioral eyeblink motor response occurs in brainstem and cerebellum Lavond 1993, 1996;Krupa et al 1993;Krupa et al 1996;Clark et al 1992, this issue). Permanent and reversible lesion studies as well as anatomical pathway tracing studies have produced a growing body of evidence describing the circuitry of the eye-blink response and the flow of learning-related unit activity within that circuitry.…”
Section: Introductionmentioning
confidence: 99%